Effect of magnetic field on THz radiation generation by self-focusing of a super Gaussian laser beam in a rippled density plasma - Mitra Amouamouha; Farhad Bakhtiari; Bijan Ghafary (AIP Advances)
Over the past three decades, much attention has been devoted to improving new methods to generate terahertz (THz) radiation. By providing ponderomotive nonlinearity in ionized plasma, the excitation of nonlinearity by laser-based techniques has emerged as a promising way for THz generation. In this paper, the concept of self-focusing of super-Gaussian laser beams has been introduced as an optimal way to generate THz radiation in plasma with a particular outlook toward the effect of applying a magnetic field to the plasma. Our analysis considers expanding the dielectric function and its higher order terms as well as paraxial ray approximation. As can be seen, magnetic field is an appropriate tool to increase the efficiency of THz self-focusing by inducing the resonance effect.